2000
DOI: 10.1159/000015518
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel β-tubulin subfamily with one member (TUBB4Q) located near the telomere of chromosome region 4q35

Abstract: The human β-tubulin supergene family consists of several isotypes with many associated pseudogenes. Here we report the identification of yet another β-tubulin sequence designated TUBB4Q. This tubulin maps 80 kb proximal to the facioscapulohumeral muscular dystrophy (FSHD1) associated D4Z4 repeats on chromosome 4q35. The genomic structure contains four exons encoding a putative protein of 434 amino acids. The TUBB4Q nucleotide and protein sequence show 87% and 86% homology to β2-tubulin, respectively. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…The copy at 4q35, however, appears to be conserved throughout evolution, as homologues have been identified in mouse [42], Fugu rubripes and Caenorhabditis elegans [43]. A putative gene has been also identified that maps 80 kb centromeric to D4Z4 on chromosome 4q35 [44]. This gene, TUBB4Q, is part of the b-tubulin supergene family and encodes a putative protein of 434 amino acids that shares 87 % homology with b2-tubulin.…”
Section: The Fshd Region On Chromosome 4q35 Contains Genes and Pseudomentioning
confidence: 99%
“…The copy at 4q35, however, appears to be conserved throughout evolution, as homologues have been identified in mouse [42], Fugu rubripes and Caenorhabditis elegans [43]. A putative gene has been also identified that maps 80 kb centromeric to D4Z4 on chromosome 4q35 [44]. This gene, TUBB4Q, is part of the b-tubulin supergene family and encodes a putative protein of 434 amino acids that shares 87 % homology with b2-tubulin.…”
Section: The Fshd Region On Chromosome 4q35 Contains Genes and Pseudomentioning
confidence: 99%
“…The high allelic sequence variability of TUBB4Q and the lack of expression of this gene suggest it may be a pseudogene. 28 In the past, another candidate gene for FSHD was identified at 120 kb proximal to D4Z4: FRG1 (FSHD Region Gene 1). This gene is ubiquitously transcribed and encodes a protein that seems to be involved in RNA processing.…”
mentioning
confidence: 99%
“…The TUBB4Q gene is a putative novel member of the betatubulin gene family, which was identified following exon trapping and subsequent computer analysis to predict a full length cDNA. 25 van Geel et al 25 proposed that TUBB4Q is a pseudogene, as they found no evidence that the gene was transcriptionally active following RT-PCR from a wide range of tissues. No EST sequences for TUBB4Q were identified, supporting the suggestion that this represents a pseudogene.…”
Section: Discussionmentioning
confidence: 99%